Continuous Visual Focal Status Epilepticus as the Primary Presentation of NMDA-R and GAD65-R Autoimmune Epilepsy - Paredes-Aragón, Elma M.; Valdéz-Ruvalcaba, Héctor E.; Santos-Peyret, Andrea; Cisneros-Otero, Marcela; Medina-Rioja, Raúl; Orozco-Suárez, Sandra; Hernandez, Miriam M.; Breda-Yepes, Michele D. L.; Rivas-Alonso, Verónica; Flores-Rivera, José J.; Martínez-Juárez, Iris E. (Frontiers in Neurology, 2020)
Epilepsia partialis continua (EPC) has changed in its clinical and pathophysiologic definition throughout time. Several etiologies have been described in addition to classic causes of EPC. The following case depicts a young woman that had a peculiar onset of epilepsy with a continuous visual aura becoming a form of chronic recurrent and non- progressive EPC; patient was initially misdiagnosed as a non-neurological entity (assumed psychiatric in origin) and finally an immune-mediated epilepsy was diagnosed and EEG showed focal status epilepticus during evolution. Once diagnosis was achieved, and immune treatment established, the patient is seizure free. Early identification of an immune basis in patients with epilepsy is important because immunotherapy can reverse the epileptogenic process and reduce the risk of chronic epilepsy. To date, this is the only case reported with EPC manifesting as a continuous visual aura associated with antiGAD-65 and anti-NMDA antibodies.